Helile formula from “Tai ping sheng hui fang”: anti-Helicobacter pylori activity, gut microbiota modulation, and inflammatory response regulation - Ling Ou; Meiyun Chen; Chang Peng; Haobo Chen; Yajie Hao; Qingchang Chen; Zhong Feng; Zhong Feng; Meicun Yao; Meicun Yao; Xianhe Kong; Xianhe Kong; et al. (Frontiers in Cellular and Infection Microbiology)
BackgroundHelicobacter pylori (HP) is a major gastric pathogen linked to chronic gastritis, peptic ulcers, and gastric cancer. The emergence of antibiotic resistance has prompted the search for alternative treatments. Helile formula, derived from the ancient “Taiping Shenghuifang,” is known to treat various degrees of diarrhea and has potential for treating gastrointestinal disorders. However, the antibacterial efficacy, material basis, and action mechanisms of the helile formula against HP remain undetermined.MethodsThe chemical constituents were analyzed using ultra-high-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) and high-performance liquid chromatography (HPLC). The in vitro anti-HP activity and underlying mechanisms were investigated through a series of assays, including the determination of minimum inhibitory concentration (MIC), N-phenyl-1-naphthylamine (NPN) uptake assay, scanning electron microscopy (SEM) to observe morphological changes, cell viability and cell adhesion activity assays, assessment of nitric oxide (NO) production, and reverse transcription-quantitative polymerase chain reaction (RT-qPCR) for gene expression analysis. For the in vivo anti-HP infection study and mechanism exploration, techniques such as hematoxylin and eosin (H&E) staining for histological examination, enzyme-linked immunosorbent assay (ELISA) for cytokine and antibody quantification, 16S ribosomal DNA (16S rDNA) sequencing for microbial community profiling, and metabolomics for global metabolite analysis were employed.ResultsMultiple constituents of helile formula, namely ellagic acid, gallic acid, chebulagic acid, chebulic acid, and corilagin, were identified. In vitro, helile formula increased bacterial outer-membrane permeability, disrupted HP structure, inhibited toxin-related genes, and suppressed cell adhesion. In male Kunming mice, helile formula effectively reversed HP-induced inflammation. It modulated key metabolites, such as adenine, panaxytriol, 4-hydroxyglutamate semialdehyde, and N-alpha-Acetyl-L-lysine. It influenced the gut microbiota, especially families like Muribaculaceae and Lactobacillaceae. Adenine, in particular, repaired HP-caused damage to GES1 cells, reduced HP - mediated cell adhesion, and inhibited HP-induced interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α) production.ConclusionThese findings demonstrated the remarkable anti-HP efficacy of the helile formula in vitro and in vivo, suggesting that the helile formula represents a highly promising therapeutic candidate for the management of HP infections.